2 potential upland rice varieties with 15 - 20% reduction in yield loss caused by low soil fertility in Madagascar - CGIAR Research Program on Rice (2021)
Variety release proceedings are ongoing together with Malagasy counterpart organization FOFIFA but are delayed due to COVID-lockdown during the crucial reproductive stage inspection period.